Uma sistemática para determinação da criticidade de equipamentos em processos industriais baseada na abordagem multicritério - Helmann, Kurtt Schamne (2008)
The present study is about the determination of the importance of the equipment in industrial processes. The determination of critical equipment for the productive process, ensuring the best use of the maintenance resources is a challenge for the Managers, because it needs to be treated differently in order to avoid human, financial and environmental damage to the company, the collaborators and to the society. In the search to help the Managers of maintenance in this challenge, this research has as objective to make available a system for the determination of importance of equipment in industrial processes. Based on the multicriteria approach of decision there are eight steps for the execution of the system, as follows: identification of the decision makers; definition of the possible alternatives, definition of the criteria which are relevant for the decision problem; evaluation of the alternatives in relation to the criteria; determination of a relative importance of the criteria; determination of the global evaluation of each alternative; analysis of sensibility; and implementation. The system allows the evaluation of each pair of equipment in relation to the multiple criteria, verifying in which criteria one equipment is more important than another one. Firstly, using the ELECTRE I method (Elimination et Chix Traduisant la Réalité) the equipment is selected in high importance. Then, with the help provided by the PROMETHEE II method (Preference Ranking Organization Method for Erichment Evaluation), the equipment is set in order from the least to the most important. One example of the use of the proposed system, is a rehearsal experiment in an industrial process of a food industry.